Location-dependent threat and associated neural abnormalities in clinical anxiety - Benjamin Suarez-Jimenez (Nature Portfolio, 2021)
Suarez-Jimenez and colleagues use a shock and safe zone experiment with fMRI imaging to examine how pathological anxiety disorders are manifested in the brain. Their findings suggest that safe and dangerous zones within the experiment alter activation in different brain regions.